Outer wall anti-crack mortar for plateau areas
By using nanomaterials such as carbon nanotubes and nanosilicon dioxide in the exterior wall crack-resistant mortar in the plateau area, the problem of insufficient bond strength and impermeability pressure in the plateau area is solved, and better bonding strength and durability are achieved.
Patent Information
- Application Number
- CN202411818312.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
In plateau areas, due to the large temperature difference between day and night in the region, the dry climate and strong sunshine, the bonding strength and anti-seepage pressure of the mortar are insufficient, which affects the adhesion between the plaster layer and the base layer, and the mechanical properties and durability of the mortar.
A crack-resistant mortar for exterior walls for plateau areas is used, and its formulation includes silicate cement with a strength grade of 42.5MPa of 28 days, blends (such as fly ash, slag powder and limestone powder), natural or artificial sand, carbon nanotubes, nanosilica, water retention agent, gas induction agent, premature strength agent, water reducing agent and fiber. These nanomaterials improve the compactness and durability of the mortar by enhancing the hydration degree of cement.
In the unfavorable construction environment in the plateau area, the bonding strength and anti-seepage pressure of the mortar are improved, the good bonding force between the plaster layer and the base layer is ensured, and the mechanical properties and durability of the mortar are significantly improved, reducing the risk of shedding.
Smart Images

Figure BDA0005182447440000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mortar, and in particular to an anti-cracking mortar for exterior walls used in plateau areas. Background Art
[0002] As the outer surface of the main structure, plastering not only maintains the main structure of the building, but also increases the decorative beauty of the building. The construction quality of the plastering project is very important to the overall quality of the building. However, during the construction process, due to the characteristics of wet work and high labor intensity, and the fact that its construction quality is greatly affected by human factors, there are relatively more problems in the use of the plastering project or the acceptance of the project completion. Especially in plateau areas, due to the special construction environment such as large temperature difference between day and night, dry climate, and strong sunshine, the dry weather during plastering causes the base wall to dry faster after watering, affecting the adhesion between the plaster layer and the base layer; the shrinkage stress of the base material is different, and no corresponding measures are taken or the measures taken are not in place during construction, resulting in linear cracks in the plaster surface layer; low humidity and low air pressure will cause the degree of cement hydration to decrease, the content of hydration products to decrease, affecting the mechanical properties and durability of the mortar; the plaster surface is frozen and alkali-returned, etc. Summary of the invention
[0003] In view of the deficiencies in the prior art, the purpose of the present invention is to provide an anti-cracking mortar for exterior walls in plateau areas, so as to solve the problem in the prior art that the bonding strength and anti-seepage pressure of the mortar are insufficient for plateau areas.
[0004] To achieve the above object, the present invention adopts the following technical solution: an anti-cracking mortar for exterior walls in plateau areas, comprising the following components calculated by weight:
[0005] 200-400 parts of cement;
[0006] 10 to 300 parts of admixture;
[0007] 400-650 parts of sand;
[0008] 0.5-5 parts of carbon nanotubes;
[0009] 5-10 parts of nano silicon dioxide;
[0010] Water-retaining agent 0.1-0.5 parts;
[0011] Air entraining agent 0.1-0.5 parts;
[0012] 1 to 3 parts of early strength agent;
[0013] Water reducing agent 0.3-1.0 part;
[0014] 2 servings of fiber.
[0015] Furthermore, the cement is silicate cement with a 28-day strength grade of 42.5 MPa.
[0016] Furthermore, the admixture is one or more of fly ash, slag powder and limestone powder. This admixture can react with the partial hydration product of cement to further generate more calcium silicate hydrate. The generated calcium silicate hydrate will further fill the pores of the cement hardened body, increase the density of the mortar, help improve the mechanical properties of the exterior wall anti-cracking mortar, and resist the erosion of corrosive media to improve durability. At the same time, these admixtures have different particle gradations, forming a grading effect in the exterior wall anti-cracking mortar, optimizing the construction and water retention of the exterior wall anti-cracking mortar. And this admixture is lower in carbon and lower in price than silicate cement, and has more environmental protection properties and cost advantages.
[0017] Furthermore, the sand is natural sand or artificial sand, the mud content of which is calculated as weight percentage <0.5%, and the particle size distribution is: 20 mesh sieve residue is 0, 40 mesh sieve residue >65%, 80 mesh sieve residue >85, 150 mesh sieve residue >96%.
[0018] Furthermore, the carbon nanotubes have a diameter ranging from 6 to 13 nm and a length ranging from 2.5 to 25 μm.
[0019] Furthermore, the particle size of the nano silicon dioxide is 10 to 20 nm, and the specific surface area is 194 to 206 m2 / g.
[0020] Furthermore, the water retaining agent is hydroxypropyl methylcellulose and / or hydroxyethyl methylcellulose, and the viscosity thereof is 40000-150000 mPa·s.
[0021] Furthermore, the air entraining agent is one or more of rosin resins, alkyl and alkyl aromatic sulfonic acids, fatty alcohol sulfonates and saponins.
[0022] Furthermore, the early strength agent is one or more of sodium sulfate, calcium formate and lithium carbonate, and the water reducer is a melamine-based water reducer or a polycarboxylic acid-based water reducer with a water reduction rate of ≥20%.
[0023] Furthermore, the fibers are polypropylene cellulose with a length of 6 to 18 mm.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] This exterior wall anti-cracking mortar is mainly used in plateau areas. Carbon nanotubes and nano-silica are mainly used for nano-modification of cement-based mortar. In plateau environments, low humidity and low air pressure will cause the degree of cement hydration to decrease, the content of hydration products to decrease, and affect the mechanical properties and durability of the mortar. After adding carbon nanotubes and nano-silica for nano-modification, the degree of cement hydration in low humidity and low humidity and low pressure environments can be improved. This is mainly because these nanomaterials can serve as crystallization centers for cement hydration products, providing more effective surface area for the precipitation and growth of hydration products, shortening the acceleration period, improving the early cement hydration degree, compacting the microstructure, reducing early water evaporation, ensuring the humidity environment inside the specimen, reducing the risk of early water seepage in the system, and improving the homogeneity and workability of the system. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below through specific embodiments:
[0027] Example 1
[0028] Weigh 200 parts of cement, 10 parts of admixture, 400 parts of sand, 0.5 parts of carbon nanotubes, 5 parts of nano-silicon dioxide, 0.1 parts of water retaining agent, 0.1 parts of air entraining agent, 1 part of early strength agent, 0.3 parts of water reducing agent and 2 parts of fiber;
[0029] Then, cement, admixture, carbon nanotubes, nano-silicon dioxide, water-retaining agent, air-entraining agent, early strength agent and water-reducing agent are added into the mixer and stirred evenly;
[0030] Then add sand and fiber into the mixer and mix well to complete the preparation of dry mix.
[0031] In this embodiment, the cement is silicate cement with a 28-day strength grade of 42.5 MPa, and the admixture is fly ash; the sand is natural sand, and its mud content is 0.3% by weight, and the particle size distribution is: 0% on a 20-mesh sieve, 70% on a 40-mesh sieve, 88% on a 80-mesh sieve, and 97% on a 150-mesh sieve; the diameter of the carbon nanotubes ranges from 6 to 13 nm, and the length ranges from 2.5 to 25 μm; the particle size of the nano-silicon dioxide ranges from 10 to 20 nm, and the specific surface area ranges from 194 to 206 m 2 / g; the water retaining agent is hydroxypropyl methylcellulose, and its viscosity is 40000Pa·s; the air entraining agent is rosin resin, such as sodium rosin acid; the early strength agent is sodium sulfate, the water reducing agent is a melamine water reducing agent with a water reducing rate of ≥20%, and the fiber is polypropylene cellulose with a length of 6 to 18 mm.
[0032] Example 2
[0033] Weigh 300 parts of cement, 150 parts of admixture, 550 parts of sand, 2.5 parts of carbon nanotubes, 7.5 parts of nano-silicon dioxide, 0.25 parts of water retaining agent, 0.3 parts of air entraining agent, 2 parts of early strength agent, 0.6 parts of water reducing agent and 2 parts of fiber;
[0034] Then, cement, admixture, carbon nanotubes, nano-silicon dioxide, water-retaining agent, air-entraining agent, early strength agent and water-reducing agent are added into the mixer and stirred evenly;
[0035] Then add sand and fiber into the mixer and mix well to complete the preparation of dry mix.
[0036] In this embodiment, the cement is silicate cement with a 28-day strength grade of 42.5 MPa, and the admixture is slag powder; the sand is artificial sand, and its mud content is 0.4% by weight, and the particle size distribution is: 0% on a 20-mesh sieve, 68% on a 40-mesh sieve, 87% on a 80-mesh sieve, and 97% on a 150-mesh sieve; the diameter of the carbon nanotubes ranges from 6 to 13 nm, and the length ranges from 2.5 to 25 μm; the particle size of the nano-silicon dioxide ranges from 10 to 20 nm, and the specific surface area ranges from 194 to 206 m 2 / g; the water retaining agent is hydroxyethyl methyl fiber, and its viscosity is 80000Pa·s; the air entraining agent is alkyl and alkyl aromatic hydrocarbon sulfonic acid, such as alkyl and alkyl aromatic hydrocarbon sulfonic acid is sodium dodecylbenzene sulfonate; the early strength agent is calcium formate, the water reducing agent is a polycarboxylic acid water reducing agent with a water reducing rate of ≥20%, and the fiber is polypropylene cellulose with a length of 6 to 18 mm.
[0037] Example 3
[0038] Weigh 400 parts of cement, 300 parts of admixture, 650 parts of sand, 5 parts of carbon nanotubes, 10 parts of nano-silicon dioxide, 0.5 parts of water retaining agent, 0.5 parts of air entraining agent, 3 parts of early strength agent, 1 part of water reducing agent and 2 parts of fiber;
[0039] Then, cement, admixture, carbon nanotubes, nano-silicon dioxide, water-retaining agent, air-entraining agent, early strength agent and water-reducing agent are added into the mixer and stirred evenly;
[0040] Then add sand and fiber into the mixer and mix well to complete the preparation of dry mix.
[0041] In this embodiment, the cement is silicate cement with a 28-day strength grade of 42.5 MPa, and the admixture is slag powder and limestone powder in a mass ratio of 1:1; the sand is artificial sand, and its mud content is 0.4% by weight, and the particle size distribution is: 20 mesh sieve residue is 0, 40 mesh sieve residue is 68%, 80 mesh sieve residue is 87%, and 150 mesh sieve residue is 97%; the diameter range of carbon nanotubes is 6 to 13 nm, and the length is 2.5 to 25 μm; the particle size of nano-silicon dioxide is 10 to 20 nm, and the specific surface area is 194 to 206 m 2 / g; the water retaining agent is hydroxypropyl methylcellulose and hydroxyethyl methylcellulose in a mass ratio of 1:1, and the viscosity thereof is 150000Pa·s; the air entraining agent is fatty alcohol sulfonates and saponins in a mass ratio of 1:1, for example, the fatty alcohol sulfonates are sodium fatty alcohol polyoxyethylene sulfonate, and the saponins are triterpenoid saponins; the early strength agent is calcium formate and lithium carbonate in a mass ratio of 1:1, the water reducing agent is a polycarboxylic acid water reducing agent with a water reducing rate ≥20%, and the fiber is polypropylene cellulose with a length of 6 to 18 mm.
[0042] Example 4
[0043] Weigh 250 parts of cement, 250 parts of admixture, 450 parts of sand, 4 parts of carbon nanotubes, 8 parts of nano-silicon dioxide, 0.4 parts of water retaining agent, 0.4 parts of air entraining agent, 2.5 parts of early strength agent, 0.8 parts of water reducing agent and 2 parts of fiber;
[0044] Then, cement, admixture, carbon nanotubes, nano-silicon dioxide, water-retaining agent, air-entraining agent, early strength agent and water-reducing agent are added into the mixer and stirred evenly;
[0045] Then add sand and fiber into the mixer and mix well to complete the preparation of dry mix.
[0046] In this embodiment, the cement is silicate cement with a 28-day strength grade of 42.5 MPa, and the admixture is slag powder, limestone powder and fly ash in a mass ratio of 1:1:1; the sand is artificial sand, and its mud content is 0.4% by weight, and the particle size distribution is: 20 mesh sieve residue is 0, 40 mesh sieve residue is 68%, 80 mesh sieve residue is 87%, and 150 mesh sieve residue is 97%; the diameter range of carbon nanotubes is 6-13nm, and the length is 2.5-25μm; the particle size of nano silicon dioxide is 10-20nm, and the specific surface area is 194-206m 2 / g; the water retaining agent is hydroxyethyl methyl fiber, and its viscosity is 120000Pa·s; the air entraining agent is fatty alcohol sulfonates, saponins and rosin resins in a mass ratio of 1:1:1, for example, the fatty alcohol sulfonates are sodium fatty alcohol polyoxyethylene sulfonate, the saponins are triterpenoid saponins, and the rosin resins are sodium rosin acid; the early strength agent is sodium sulfate, calcium formate and lithium carbonate in a mass ratio of 1:1:1, the water reducing agent is a polycarboxylic acid water reducing agent with a water reducing rate ≥20%, and the fiber is polypropylene cellulose with a length of 6 to 18 mm.
[0047] Example 5
[0048] Weigh 350 parts of cement, 100 parts of admixture, 450 parts of sand, 2 parts of carbon nanotubes, 6 parts of nano-silicon dioxide, 0.2 parts of water retaining agent, 0.3 parts of air entraining agent, 1.5 parts of early strength agent, 0.5 parts of water reducing agent and 2 parts of fiber;
[0049] Then, cement, admixture, carbon nanotubes, nano-silicon dioxide, water-retaining agent, air-entraining agent, early strength agent and water-reducing agent are added into the mixer and stirred evenly;
[0050] Then add sand and fiber into the mixer and mix well to complete the preparation of dry mix.
[0051] In this embodiment, the cement is silicate cement with a 28-day strength grade of 42.5 MPa, and the admixture is limestone powder; the sand is artificial sand, and its mud content is 0.4% by weight, and the particle size distribution is: 0% on a 20-mesh sieve, 68% on a 40-mesh sieve, 87% on a 80-mesh sieve, and 97% on a 150-mesh sieve; the diameter of the carbon nanotubes ranges from 6 to 13 nm, and the length ranges from 2.5 to 25 μm; the particle size of the nano-silicon dioxide ranges from 10 to 20 nm, and the specific surface area ranges from 194 to 206 m 2 / g; the water retaining agent is hydroxypropyl methylcellulose, and its viscosity is 100000Pa·s; the air entraining agent is a saponin, for example, the saponin is a triterpenoid saponin; the early strength agent is lithium carbonate, the water reducing agent is a polycarboxylic acid water reducing agent with a water reducing rate of ≥20%, and the fiber is a polypropylene cellulose with a length of 6 to 18 mm.
[0052] Comparative Example 1
[0053] The difference from Example 5 is that no carbon nanotubes are added and the amount of nano-silicon dioxide added is 8 parts.
[0054] Comparative Example 2
[0055] The difference from Example 5 is that no nano-silicon dioxide is added and the amount of carbon nanotubes added is 8 parts.
[0056] The mixed dry materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2 were mixed with water at a mass ratio of 4:1 to form exterior wall anti-cracking mortar. In Xiangluolila Town, Daola County, Ganzi Prefecture, the detection method in JGJ / T70-2009 was used to detect the exterior wall anti-cracking mortars to obtain the detection data shown in Table 1.
[0057]
[0058] Table 1
[0059] It can be seen from Table 1 that the carbon nanotubes and nano-silicon dioxide in the exterior wall anti-cracking mortar prepared in the present invention have a synergistic effect, and the specific formula in Example 4 has more advantages in the tested performance.
[0060] The exterior wall renovation project was carried out in Xiangluolila Town, Daola County, Ganzi Prefecture, a plateau area: In the exterior wall renovation of the stone and wood structure Tibetan houses in the plateau area, the original wall surface was made of local stone masonry, and the following processes were used to transform it into a wet-pasted exterior wall based on the stone masonry wall. The specific transformation procedures are as follows: base cleaning, base sprinkling and wetting (3 times), adhesive brushing, line drawing, full hanging and locking of wire mesh, drilling, hole cleaning, horizontal angle steel installation, vertical round steel bar welding, rust prevention treatment, first anti-cracking mortar finishing, second anti-cracking mortar finishing, stone grooving and drilling, copper wire threading, wire pulling, stone paving, copper wire fixing, water sprinkling and maintenance, stone jointing and wall cleaning; the exterior wall anti-cracking mortar used in the above-mentioned first anti-cracking mortar finishing and second anti-cracking mortar finishing process is the mixed dry material prepared by the present invention and water mixed according to a mass ratio of 4:1; it overcomes the unfavorable construction environment in plateau areas due to large temperature difference between day and night, dry climate and strong sunshine, and has good bonding strength with the exterior wall stone, and the formed exterior wall plastering layer has excellent durability, reducing the risk of falling off.
[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. An anti-cracking mortar for exterior walls in plateau areas, characterized in that: The following components are included in parts by weight: 200-400 parts of cement; 10 to 300 parts of admixture; 400-650 parts of sand; 0.5-5 parts of carbon nanotubes; 5-10 parts of nano silicon dioxide; Water-retaining agent 0.1-0.5 parts; Air entraining agent 0.1-0.5 parts; 1 to 3 parts of early strength agent; Water reducing agent 0.3-1.0 part; 2 servings of fiber.
2. The anti-cracking mortar for exterior walls in plateau areas according to claim 1 is characterized in that: The cement is silicate cement with a 28-day strength grade of 42.5 MPa.
3. The anti-cracking mortar for exterior walls in plateau areas according to claim 1 is characterized in that: The admixture is one or more of fly ash, slag powder and limestone powder.
4. The anti-cracking mortar for exterior walls in plateau areas according to claim 1 is characterized in that: The sand is natural sand or artificial sand, and its mud content is calculated as weight percentage <0.5%, and its particle size distribution is: 20 mesh sieve residue is 0, 40 mesh sieve residue is >65%, 80 mesh sieve residue is >85%, and 150 mesh sieve residue is >96%.
5. The anti-cracking mortar for exterior walls in plateau areas according to claim 1 is characterized in that: The carbon nanotubes have a diameter ranging from 6 to 13 nm and a length ranging from 2.5 to 25 μm.
6. The anti-cracking mortar for exterior walls in plateau areas according to claim 1 is characterized in that: The particle size of the nano silicon dioxide is 10-20 nm, and the specific surface area is 194-206 m 2 / g.
7. The anti-cracking mortar for exterior walls in plateau areas according to claim 1 is characterized in that: The water retaining agent is hydroxypropyl methylcellulose and / or hydroxyethyl methylcellulose, and its viscosity is 40000-150000 mPa·s.
8. The anti-cracking mortar for exterior walls in plateau areas according to claim 1 is characterized in that: The air entraining agent is one or more of rosin resins, alkyl and alkyl aromatic sulfonic acids, fatty alcohol sulfonates and saponins.
9. The anti-cracking mortar for exterior walls in plateau areas according to claim 1, characterized in that: The early strength agent is one or more of sodium sulfate, calcium formate and lithium carbonate, and the water reducing agent is a melamine water reducing agent or a polycarboxylic acid water reducing agent with a water reducing rate of ≥20%.
10. The anti-cracking mortar for exterior walls in plateau areas according to claim 1, characterized in that: The fibers are polypropylene cellulose with a length of 6 to 18 mm.